[RETRACTED] A Discourse Analysis of German Fairy Tale “Rapunzel” Written by the Brothers Grimm - Andi Tenrisanna Syam (Universitas Cokroaminoto Palopo, 2018)
This article has been retracted due to double publication found at https://journal.unnes.ac.id/nju/index.php/LC/article/view/14943 Apologies are offered to readers of the journal that this was not detected during the submission process.